Comprehensive characterization of modern industrial Argentinian paints for improved chronological painting attribution - Castellá, Florencia; Pérez Estebanez, Marta; Reinoso, Maria Elba; Schilling, Michael; Khanjian, Herant; Learner, Tom; Fernandez Niello, Jorge Oscar; Tascon, Marcos; Marte, Fernando (Elsevier France-Editions Scientifiques Medicales Elsevier, 2024)
Fil: Castellá, Florencia. Universidad Nacional de San Martín. Escuela de Hábitat y Sostenibilidad;